Rural institutions and producer organizations in imperfect markets: experiences from producer marketing groups in semi-arid eastern Kenya - Shiferaw, Bekele A.; Obare, G. A.; Muricho, Geoffrey (International Food Policy Research Institute, 2006)
Many countries in sub-Saharan Africa have liberalized markets to improve efficiency and enhance market linkages for smallholder farmers. The expected positive response by the private sector in areas with limited market infrastructure has however been disappointing. The functioning of markets is constrained by high transaction costs and coordination problems along the production-to-consumption value chain. New kinds of institutional arrangements are needed to reduce these costs and fill the vacuum left when governments withdrew from markets in the era of structural adjustments. One of these institutional innovations has been the strengthening of producer organizations and formation of collective marketing groups as instruments to remedy pervasive market failures in rural economies. The analysis presented here with a case study from eastern Kenya has shown that while collective action – embodied in Producer Marketing Groups (PMGs) – is feasible and useful, external shocks and structural constraints that limit the volume of trade and access to capital and information require investments in complementary institutions and coordination mechanisms to exploit scale economies. The effectiveness of PMGs was determined by the level of collective action in the form of increased participatory decision making, member contributions and initial start-up capital. Failure to pay on delivery, resulting from lack of capital credit, is a major constraint that stifles PMG competitiveness relative to other buyers. These findings call for interventions that improve governance and participation; mechanisms for improving access to operating capital; and effective strategies for risk management and enhancing the business skills of the PMGs.